2001
DOI: 10.1034/j.1399-302x.2001.160410.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of acidified nitrite on periodontal bacteria

Abstract: The antimicrobial agent nitric oxide (NO) is formed in the mouth and its concentration is directly related to salivary nitrite, which in turn is related to dietary nitrate intake. The aim of this study was to determine whether nitrite under acidic conditions will have an inhibitory effect, possibly occurring through NO production, on the periodontal disease pathogens Fusobacterium nucleatum, Eikenella corrodens and Porphyromonas gingivalis. Whereas the growth of these organisms was inhibited by a more acid pH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 15 publications
0
48
0
4
Order By: Relevance
“…The antimicrobial activity of nitrites in cured meat products is also enhanced from other antimicrobial hurdles such as heat treatment, pH, salt, water activity (a w ), redox potential and other curing ingredients (Tompkin, 2005). Several studies indicated that nitrites inhibit bacteria more effectively at low pH (Roberts, 2005;Allaker et al, 2001). Other components, such as ascorbate or isoascorbate / erythorbate and also cysteine, may enhance the antibotulinum efficacy of nitrites in cured meat by sequestering metal ions (Tompkin et al, 1978).…”
Section: Microbiological Safetymentioning
confidence: 99%
“…The antimicrobial activity of nitrites in cured meat products is also enhanced from other antimicrobial hurdles such as heat treatment, pH, salt, water activity (a w ), redox potential and other curing ingredients (Tompkin, 2005). Several studies indicated that nitrites inhibit bacteria more effectively at low pH (Roberts, 2005;Allaker et al, 2001). Other components, such as ascorbate or isoascorbate / erythorbate and also cysteine, may enhance the antibotulinum efficacy of nitrites in cured meat by sequestering metal ions (Tompkin et al, 1978).…”
Section: Microbiological Safetymentioning
confidence: 99%
“…Various periodontopathogens, such as A. actinomycetemcomitans and P. gingivalis, have been shown to upregulate iNOS expression and NO production by a variety of cells, including mouse macrophages (37-39). Several reports reveal that NO is required for antimicrobial activity and immune modulation (40). Moreover, significantly increased iNOS expression by gingival macrophages, endothelial cells, and keratinocytes is observed in patients with periodontal disease, including localized aggressive periodontitis (41)(42)(43)(44)(45)(46).…”
Section: Figmentioning
confidence: 99%
“…70 NO is formed in oral cavity of health individuals and its concentration is directly related to salivary nitrite, 71 which in turn is associated to dietary nitrate intake, and intraoral pH level. 72 It has been…”
Section: 66mentioning
confidence: 99%
“…72 However, some factors in saliva suppress the synthesis NO or destroy already produced NO. The most important molecule, which suppresses NO productions, is arginase in saliva.…”
Section: 66mentioning
confidence: 99%